2012
DOI: 10.1111/j.1471-0528.2012.03394.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low to moderate prenatal alcohol exposure in early pregnancy on IQ in 5‐year‐old children

Abstract: Objective To examine the effects of low to moderate maternal alcohol consumption during early pregnancy on children's intelligence (IQ) at age 5 years.Design Prospective follow-up study.Setting Neuropsychological testing in four Danish cities 2003-2008. Population A cohort of 1628 women and their children sampled from the Danish National Birth Cohort.Methods Participants were sampled based on maternal alcohol consumption during pregnancy. At 5 years of age, children were tested with the Wechsler Preschool a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 31 publications
4
73
0
1
Order By: Relevance
“…Multivariate analysis showed no statistically significant effects of average weekly alcohol consumption, either individually or in combination on child's intelligence, attention and executive function [36]. These results replicate findings from separate analyses of alcohol consumption on child's intelligence, attention and executive function [31,35]. In summary, more compelling and stronger evidence is needed to evaluate the effect of low-to-moderate levels drinking during pregnancy.…”
Section: Criteria For Inclusion Of Studies Into the Reviewsupporting
confidence: 72%
See 3 more Smart Citations
“…Multivariate analysis showed no statistically significant effects of average weekly alcohol consumption, either individually or in combination on child's intelligence, attention and executive function [36]. These results replicate findings from separate analyses of alcohol consumption on child's intelligence, attention and executive function [31,35]. In summary, more compelling and stronger evidence is needed to evaluate the effect of low-to-moderate levels drinking during pregnancy.…”
Section: Criteria For Inclusion Of Studies Into the Reviewsupporting
confidence: 72%
“…Additionally the results of the studies on the impact of low to moderate alcohol consumption on IQ are inconclusive. Lower IQ scores were observed in some [33], but not all studies [34,35]. When reviewing the epidemiological studies on the influence of exposure to environmental factors and neurodevelopment in children, it is important to take into account the current limitations of these studies resulting from inadequacies in exposure and outcome assessment, study design and analysis.…”
Section: Summary Of the Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Light-to-moderate drinking in pregnancy is still controversial. Some studies have found that this level of alcohol consumption may lead to adverse neurodevelopmental effects (D'Onofrio et al 2007;Flak et al 2014), whereas other studies have established no such effects (Falgreen Eriksen et al 2012;Skogerbo et al 2012;Underbjerg et al 2012). Owing to the demonstrated potential for harm to the fetus, most health organizations advocate abstinence from alcohol throughout pregnancy (Centers for Disease Control and Prevention 2005; Public Health Agency of Canada 2012).…”
Section: Introductionmentioning
confidence: 99%